PENGARUH WADAH DAN AERASI TERHADAP PERTUMBUHAN TETRASELMIS CHUII PADA SKALA KULTUR INTERMEDIATE DI BALAI PERIKANAN BUDIDAYA AIR PAYAU SITUBONDO, JAWA TIMUR - MUHAMMAD SUMSANTO; NURI MUAHIDDAH (GANEC SWARA, 2023)
In the effort of developing marine aquaculture, the hatchery stage is essential. During this stage, natural feed cannot be separated, because larvae generally are plankton feeders. Natural feed for fish is organisms in the water, which can be plants like phytoplankton and animals like zooplankton. With the increasing aquaculture activities in Indonesia, the demand for natural feed also increases. Organisms needed for natural feed, such as phytoplankton, can be obtained by collecting them from nature. However, to meet the availability of natural feed in fish farming, it is now done by cultivating them so that natural feed can be available sustainably. The method used in this research is a qualitative method by observing the growth and water quality of Tetraselmis chuii culture. Based on the research results, the best treatment for culturing Tetraselmis chuii is using Erlenmeyer culture with aeration because the cell growth reaches 700 x 10 4 cells/ml. Data on water quality results in intermediate Tetraselmis chuii culture are good for growth. The water quality in the culture tank is relatively stable at 25°C, pH 8, salinity ranges between 33-34 ppt, nitrate ranges between 13.6-17.8 ppm, and phosphate ranges between 2.32-7.6 ppm. The problem that occurred during intermediate culture is the contamination of other organisms. Prevention against contamination is by maintaining the sterility and specifications of the equipment used.